Practicing Human Resource strategy: Understanding the relational dynamcis in strategic HR work by means of a narrative approach - Stephanie Kaudela-Baum; Nada Endrissat (Zeitschrift für Personalforschung (ZfP), 2009)
This article presents the results of a qualitative research project aimed at examining how Human Resource (HR) practitioners interpret HR strategy and strategic change. We will illustrate how they develop HR strategy by relying on a system of shared practices which, in turn, constitute the underlying relational dynamics. We argue that HR strategy is embedded in a (rhetorical) network of middle and top managers from HR departments and corresponding operational departments. This implies that HR strategy happens in a social process, more precisely in practices-in-use. Drawing on a systemic constructionist framework, the article discusses the nature of practices-in-use and presents findings from an inductive analysis of a qualitative HR study. The qualitative nature enabled us to shed light on previously neglected aspects of the field of strategic human resource management (SHRM). We will outline our research approach and method in detail and discuss its suitability for studying SHRM issues. The article concludes by proposing a new understanding of SHRM that will hopefully prove to be fruitful both in theory and practice. – – In diesem Artikel werden die Ergebnisse einer qualitativen Studie vorgestellt, die sich zum Ziel gesetzt hat, das Konstrukt 'Personalstrategie' als Managementpraxis im Sinne von kulturabhängigen, kontingenten Beziehungs-, Kommunikations- und Sinnprozessen zu rekonstruieren. Der Artikel liefert eine dichte Beschreibung, wie sich Personalstrategie durch ein System geteilter Praktiken und damit einhergehenden Beziehungsdynamiken im Kontext strategischer Wandelsituationen formt, d.h. wie Personalstrategie von HR Praktikern gedacht und erlebt wird. Das heisst, Personalstrategien gründen in sozialen Prozessen, genauer gesagt in 'practices-inuse'. Die aus narrativen Interviews extrahierten Praktiken und beziehungsdynamischen Aspekte werden aus einer systemisch-konstruktivistischen Forschungsperspektive entfaltet. Die genaue Vorgehensweise unseres qualitativen Ansatzes sowie seine Vorteile im Vergleich zu herkömmlichen quantitativen Studien im Bereich des strategischen Human Resource Managements (SHRM) werden aufgezeigt und diskutiert. Ein neues Verständnis von SHRM wird skizziert, das sich hoffentlich als nützlich für die Anwendung in Theorie und Praxis erweisen wird.
Keywords: 330; strategic human resource management; systemic constructionist approach; practice perspective; narrative method; inductive analysis; Personalmanagement